The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1136/bjo.2007.133900
|View full text |Cite
|
Sign up to set email alerts
|

Changes in meibomian fatty acids and clinical signs in patients with meibomian gland dysfunction after minocycline treatment

Abstract: This study showed better tear film stability after minocycline treatment and a biological effect on meibomian fatty acid composition in MGD patients. Minocycline was more effective than lid hygiene alone. Both interventions partly corrected fatty acid composition abnormalities. Among the fatty acids, isoC20 could be a biological marker of MGD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
60
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 21 publications
1
60
0
2
Order By: Relevance
“…Therefore, they could not be a major source of the LCFA and VLCFA either. Our current findings show that such a source is Chl-E. Interestingly, our data show that the longest fatty acid detected in Chl-E of human meibum has up to 34 carbons, far longer than 26 carbons reported by Joffre et al (29,30) and, possibly, even longer than that if the Chlcontaining HPLC peaks 19 and 20 are indeed Chl-E. Also, a large portion of the LCFA and VLCFA were monounsaturated. This discrepancy has most likely to do with the well-known fact that long chain fatty acids are unstable under the conditions of GC-MS analysis and quickly decompose at high temperatures at which the GC columns typically operate.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Therefore, they could not be a major source of the LCFA and VLCFA either. Our current findings show that such a source is Chl-E. Interestingly, our data show that the longest fatty acid detected in Chl-E of human meibum has up to 34 carbons, far longer than 26 carbons reported by Joffre et al (29,30) and, possibly, even longer than that if the Chlcontaining HPLC peaks 19 and 20 are indeed Chl-E. Also, a large portion of the LCFA and VLCFA were monounsaturated. This discrepancy has most likely to do with the well-known fact that long chain fatty acids are unstable under the conditions of GC-MS analysis and quickly decompose at high temperatures at which the GC columns typically operate.…”
Section: Discussionmentioning
confidence: 49%
“…The VLCFA also suffer from low volatility, which is inversely proportional to their length and molecular mass. Therefore, the notable absence of VLCFA beyond C 26 for saturated compounds, and anything beyond C 18:1 for unsaturated VLCFA in the data by Joffre et al (29,30) can be related to these limitations of the GC-MS technique. The exact location and geometry of the double bonds in the structures of monounsaturated Chl-E from meibum remain to be investigated.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[25][26][27][28] It has been well documented that meibomian glands dysfunctions are associated with ocular irritation and ocular surface staining. 20,[29][30][31] Our multi-regression analysis showed that the staining score of the inferior conjunctiva and cornea were correlated with the meibomian glands dysfunction scores. These results were not too surprising because these regions are frequently in contact with the lid margins during blinking.…”
Section: Discussionmentioning
confidence: 97%